Studies on the Decay of Bamboo (Dendrooalamus striotus) during Outside Storage-degradation of Cellulose - Chandra, A.; Guha, S. R. D. (Indian Forester, 1979)
Cellulose is a major constituent of wood and constitute approximately one half of the wood substance. It occurs in fibre walls both in crystalline and amorphous forms, and is always accompanied by other polysaccharides. The total polysaccharides being called holocellulose. During outside storage the bamboos were attacked by wood destroying fungi resultiag in the loss or both holocellulose and Î±-cellulose contents, and also a reduction in the degree of polymerization both in the preservative treated and in untrtated bamboos (controls). The loss of Î±-cellulose in pentachoro-phenate treated bamboo was about 24% after a 12 months storage period, while the untreated controls showed a loss of about 31% during the same period similarly the holocellulose content was also depleted more in the control bamboos than in the preservative treated bamboos. The degree of polymerization of both the Î±-cellulose and the holocelhlose decreased consideratory during the storage period in untreated bamboos. As the storage period increased the degree of polylnerizatinn of Î±-cellulose and bolocellulose decreased gradually indicating a possible random cleavage of the molecules by the cdorbohydrates secreted by the white rot and soft rot fungi which decayed the bamboo during their outside storage.